La inclusión social por la vía del cuerpo en mujeres diagnosticadas con anorexia bulimia en la ciudad de Medellín, Colombia (2010)
ABSTRACT: This report presents the findings of a research entitled “Identity narratives about the body experience of women diagnosed with eating disorders” which was carried out in Medellín, Colombia. Objective: to recognize how the meaning given to body experience reveals the identity construction of women with eating disorders. Methodology: a qualitative approach with a multiplecase design. Cases were analyzed using procedures of the phenomenological hermeneutic method. In-depth interviews and focus groups were done. The project complied with the ethical principles for medical research involving human subjects, including the informed consent. Results: 1) self-evaluation of these women is strongly influenced by the perception of other persons; 2) there are social contexts of occurrence that stimulate the development of anorexia-bulimia; 3) three ways of configuration of anorexia-bulimia were found, namely: the aesthetic-erotic, the aesthetic-athletic, and the aesthetic-affective; 4) recovery from anorexiabulimia does not consist solely of eating, but also of allowing the patients’ body to historicize itself, that is, to show the effects of time.